Local scour at bridge pier in overtopping flows - Tan, Carissa Yue Xuan (Nanyang Technological University, 2020)
Due to the impacts of global warming, sea levels have been constantly on the rise. Furthermore, climate change has caused an increase in flood peaks during the monsoon seasons. As a result, many researches have been conducted to study the effect of pier scours. In the past, bridge structures were designed for the open channel flow condition, where the approach flow depth is below the bridge deck level. However, with the rising of sea levels and increase in flood peaks, existing bridges may become fully submerged with orifice flow condition occurring through the bridge opening, which may eventually overtop of the bridge deck. Numerous studies have been conducted on pier scours in open channel flow condition and orifice flow condition. However, there are relatively fewer researches done on overtopping flow condition in comparison to the two other flow conditions. Hence, more emphasis was made on overtopping flow condition in this study. All experiments were conducted in the hydraulics modelling laboratory with various flow conditions to find out its effects on the scour depth. The prototype was placed in the middle with varied depth to simulate different flow conditions, while keeping the flow rate and approach flow depth constant throughout the study. Three different flow conditions were considered: Open channel, Orifice, and Overtopping flow condition. Open channel flow condition occurs when the approach flow depth is below the bridge deck level such that the water flow with a free surface open to the atmosphere. Orifice flow condition occurs when the approach flow depth is at the bridge deck level, inducing a pressurised flow. Overtopping flow condition occurs when the approach flow depth surpassed the bridge deck level, i.e. overtops the bridge deck, separating the approach flow into one flowing above and one flowing under the bridge deck. From this study, the equilibrium scour depth was the deepest in overtopping flow condition. In overtopping flows, both the leading and trailing jet, as well as the upstream flow at the front of the bridge pier contributes to the increases of scour depth. An experiment was also done with an increase in the upstream length of bridge deck in overtopping flow condition. However, the results shows that with the increase in the upstream length of the bridge deck, the equilibrium scour depth decreases under the same flow condition. A possible explanation for this finding could be due to that the flow rate under the bridge deck. With the introduction of a longer upstream bridge deck length, the flow rate under the bridge deck may increase. This causes the flow velocity to decrease, hence the decrease in equilibrium scour depth.